Phage Therapy in a 16-Year-Old Boy with Netherton Syndrome - Zhvania, Pikria; Hoyle, Naomi Sulinger; Nadareishvili, Lia; Nizharadze, Dea; Kutateladze, Mzia (Frontiers in Medicine, 2017)
Netherton’s Syndrome (NS) is a rare autosomal recessive disorder, characterized by a classical triad of clinical features, including congenital ichthyosiform erythroderma, trichorrhexis invaginata, and atopic diathesis coupled with frequent bacterial infections1. The genetic basis for the disease has been recently identified with mutations in gene SPINK5 which is involved in the regulation of formation of skin barriers. We report on a 16-year-old male with all the typical manifestations of NS, including atopic diathesis and ongoing serious staphylococcal infections and allergy to multiple antibiotics whose family sought help at the Eliava Phage Therapy Center when all other treatment options were failing. Treatment with several antistaphylococcal bacteriophage preparations led to significant improvement within 7 days and very substantial changes in his symptoms and quality of life after treatment for 6 months, including return visits to the Eliava Phage Therapy Center after 3 and 6 months of ongoing use of phage at home.